METHODOLOGICAL APPROACH TO THE ELABORATION OF INDICATORS FOR QUANTIFYING THE COMPETITIVENESS OF GOODS - GUTIUM, Tatiana (Economy and Sociology, 2021)
The period of temporary economic isolation caused by the Covid-19 pandemic has affected the economies of all countries in the world. After quarantine and the gradual restoration of the activity of all economic sectors, competition in the world market will intensify. Countries will promote strategies for economic growth, improving economic security, increasing exports, and protecting domestic producers. Given the fact that resources are limited and exhaustible, it is necessary to correctly identify priority sectors when developing strategies. For this purpose, the competitiveness index can be used, since competitiveness is one of the main characteristics that allows anyone to determine its position on the market, and increasing competitiveness ensures victory in the competition. The novelty and purpose of the study is to develop two new integral indices, and to improve one symmetric index of comparative advantage developed earlier. Some of empirical and theoretical methods were used in this research: abstraction, the method of ascending from the abstract to the concrete, comparison, measurement, analysis and synthesis, economic and mathematical modelling. To identify priority sectors, the author used the developed indices to assess the competitiveness of goods, not only on the foreign market, but also on the domestic market. This study can serve economists as a tool for assessing the competitiveness of goods, identifying the strengths and weaknesses of the goods offered, in the context of developing measures to increase competitiveness, which will increase the profitability of entrepreneurship.